Rosa parks visits the Middle East: critical events in a minority arab classroom. Issue 2 (3rd April 2022) - Hayik, Rawia
ABSTRACT: When invited to respond to the story of Rosa Parks through describing whether they encountered similar events within their Israeli context, the minority Palestinian-Israeli EFL ninth-grade students in this teacher research narrated stories resonating with Rosa's story. Evident in their narratives were events that left an immense impact on them. A critical events analysis of those stories shed light on minority students' feelings, beliefs, identities, and perceptions of reality as they navigated their daily life amidst a challenging reality of marginalization and silencing. In addition to expanding the understanding of how identities of indigenous minority students are constructed through mundane everyday encounters, this article contributes to literature on using pedagogies that help students to narrate, explore and understand these encounters as a social matter.